Czy Europa zaakceptuje uprawy roślin genetycznie zmodyfikowanych? – argumenty i kontrargumenty - Jerzy Macewicz (Studia Ecologiae et Bioethicae)
This paper is a review of recent publications dealing with the consequences of the release of genetically modified (GM) crops into the environment. The summary of arguments and for and against is an attempt to summarize the debate in the media. This highly publicized issue, although only one aspect of the conflict between the biotech lobby, environmentalists, and consumers. The controversy arises from the fact that neither the benefits nor the risks of GM crops are clearly defined. The study contains a summary of claims that there is a serious potential risk to the environment of positive cultivation of GM crops, with uncertain effects, and that basic manipulation of heredity could have tragic consequences. European skepticism about GM crops increases from year to year. This paper coincides with the Polish government’s introduction of a ban on the cultivation of genetically modified maize and potatoes on Polish territory. In conclusion, while a move away from GM crops is likely, the author argues that ultimately there is no turning back.